Prilaku Sosial Politik Tuan Guru Pasca Reformasi Dalam Memajukan Pendidikan Islam Di Lombok - Udin Udin (Al-Riwayah : Jurnal Kependidikan, 2020)
This research aim to explore the political behavior of Tuan Guru in post-reformation in Lombok. This research also trie to reveal the existence of Tuan Guru in terms of the historical aspects of the cultural traditions and religious patterns of the Lombok society. This research found that Tuan Guru in Lombok has a very broad position and role, not only in the religious aspects, but also in the social, economic and political fields.